Longitudinal integrated clerkships*. (2nd January 2017) - Hudson, Judith Nicky; Poncelet, Ann N.; Weston, Kath M.; Bushnell, John A.; A Farmer, Elizabeth
Abstract: There is increased interest in longitudinal integrated clerkships (LICs) due to mounting evidence of positive outcomes for students, patients and supervising clinicians. Emphasizing continuity as the organizing principle of an LIC, this article reviews evidence and presents perspectives of LIC participants concerning continuity of care, supervision and curriculum, and continuity with peers and systems of care. It also offers advice on implementing or evaluating existing LIC programs.